Meta-analysis of Hots Science Daily Grade VIII SMP Negeri 7 Kerinci Lesson Year 2020/2021 - Wahyuni, Wahyuni (FMIPA UNNES, 2021)
The purpose of this research is to know about the Daily Deuteronomy (UH) Of Integrated Science Students Grade VIII SMP Negeri 7 Kerinci Year Point 2020/2021 which is from the higher validity, reliability, differentiation and difficulty level. This research is quantitative research with descriptive method. Mata in this study students of grade VIII SMP Negeri 7 Kerinci Year Story 2020/2021 which amounted to 50 students and objects in this study is the question and answer Key Deuteronomy (UH) Mata Sekolah IPA Terpadu VIII Class VIII SMP Negeri 7 Kerinci Year Story 2020/2021 which consists of 20 Ways of collecting data which way. Analyze data by means of spss program help version 24.0 and Microsoft Excel. From the results of the study, it can be concluded that valid question items amounted to 11 questions with a percentage of 55 percent at number 1,2,3,4,7,9,10,11,14,16,19 with criteria ≥ 0.2787, while the invalid question amounts to 9 questions with 45% points at 5,6,8,12,13,15,17,18,20 with criteria < 0.2787. Daily Deuteronomy Problem Reliability (UH) This Integrated IPA Value Currency has a Value of Cronbach’s Alpha or s 0.70 and is disp above the reliability criteria that is a matter of whether reliability is high. On the differentiation of the question that is classified as good as 45 % of the 20 points of multiple choice questions at this time high learners with low group learners. The question item which is the question which is a good differentiator or the proportion of the index derimination of the problem in the sub-district is high. And the index of difficulty of good questions that are classified as being greater than the problem that is classified as difficult is from 20 points of multiple choice questions 13 points of questions (65%) relatively easy.